Soldiers’ slang in the Polish People’s Army – the phenomenon of fala and its functional equivalents in the National People’s Army of the German Democratic Republic - Smolińska, Mariola (Papers in Linguistics, 2026)
The article presents an analysis of military slang in the Polish People’s Army (Ludowe Wojsko Polskie, LWP), with particular emphasis on the phenomenon of fala [wave] (beas- ting practices in the army) – an informal system of customs and hierarchy among recruits, dependent on the length of service. The aim of the study is to show how soldiers’ everyday language reflected their experiences related to fala during their service. The source material includes glossaries, collections of lexical items, and autobiographical accounts of former conscripts who completed compulsory military service between 1975 and 1989. The analysis focused on selected lexical items, which were compared with their functional equivalents in the military slang of the National People’s Army (Nationale Volksarmee, NVA) of the former German Democratic Republic (GDR). The adopted lexical-pragmatic comparative perspective made it possible to capture both similarities arising from similar institutional frameworks of service and differences conditioned by local linguistic and cultural contexts. The synthesis confirms the transnational character of the phenomenon of beasting in the military: analogous service frameworks in both armies fostered the emergence of comparable communicative practices and linguistic mechanisms.